2014
DOI: 10.1021/jf5036417
|View full text |Cite
|
Sign up to set email alerts
|

Use of Graphene and Gold Nanorods as Substrates for the Detection of Pesticides by Surface Enhanced Raman Spectroscopy

Abstract: This study aimed to use gold nanorods and graphene as key materials to fabricate high-performance substrates for the detection of pesticides by surface enhanced Raman spectroscopy (SERS). Three types of pesticides (azinphos-methyl, carbaryl, and phosmet) were selected. Gold nanorods have great potential to be used as a SERS substrate because it is easy to tune the surface plasmon resonance of the nanorods to the laser excitation wavelength of Raman spectroscopy. Graphene is a promising nanoscale material that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 31 publications
1
41
1
Order By: Relevance
“…41−43 This effect depends on several factors, such as the type of metal, the metal surface morphology, graphene thickness, 42,44 etc. Graphene has been integrated with various shapes of gold nanoparticles for SERS enhancement, such as arrays of gold nanodisks, 41 photonic-crystal nanocavities, 45 gold nanorods, 46 and silver, copper, or gold nanospheres 47 The effectiveness of graphene in stabilizing the SERS system of thermally grown Au and Ag nanoparticles and achieving strong enhancement has been proven, 32,47 as shown in Figure 6a,b. These studies showed that the detection limit is ∼100-fold larger with graphene coupled with the SERS system.…”
Section: Gers Meets With the Metal Substratementioning
confidence: 99%
“…41−43 This effect depends on several factors, such as the type of metal, the metal surface morphology, graphene thickness, 42,44 etc. Graphene has been integrated with various shapes of gold nanoparticles for SERS enhancement, such as arrays of gold nanodisks, 41 photonic-crystal nanocavities, 45 gold nanorods, 46 and silver, copper, or gold nanospheres 47 The effectiveness of graphene in stabilizing the SERS system of thermally grown Au and Ag nanoparticles and achieving strong enhancement has been proven, 32,47 as shown in Figure 6a,b. These studies showed that the detection limit is ∼100-fold larger with graphene coupled with the SERS system.…”
Section: Gers Meets With the Metal Substratementioning
confidence: 99%
“…An experiment by Wang et al [197] proved that ~7 nm thick Au films are the perfect SERS substrates among the different thickness of Au films, decorated on the monolayer graphene for the characterization of low concentration rhodamine molecules, providing the strongest Raman signals for molecules with the weakest photoluminescence background. All of these extraordinary advantageous properties make graphene–Au nanocomposites the perfect substrate for SERS measurements, as it has been extensively instigated in versatile applications, including sensing and molecular diagnostics, biomedical applications, agriculture, food adulteration [202], and so on. This hybrid has also been verified for the detection of single molecule interactions [184], identification of pathogenic microorganisms [203] and biomolecules [204,205], nucleic acids [206], and cancer cells [207], and even in the detection of explosives and chemical warfare agents [208].…”
Section: Graphene–gold Nanoparticle Hybrid For Biosensing and Bioimentioning
confidence: 99%
“…Nguyen et al [202] have fabricated a high performance SERS substrate by using graphene–Au films–AuNRs for the detection of three pesticides namely azinphos-methyl, carbaryl, and phosmet by SERS with LODs of approximately 5, 5, and 9 ppm, respectively. The LODs of carbaryl and phosmet meet the FAO/WHO- and EU-defined maximum residue limits, which make it a potential method in food safety applications.…”
Section: Graphene–gold Nanoparticle Hybrid For Biosensing and Bioimentioning
confidence: 99%
“…The comparisons of the SERS column for quantitative detection of phosmet in current work with the results in literature using other SERS substrates are listed in Table 1. It is summarized the present reported other techniques for phosmet detection, including surface plasmon resonance sensor [33], gas chromatography with flame photometric detection [34], gas chromatography-tandem mass spectrometry [1], enhanced chemiluminescence enzyme linked immunosorbent assay [35] and SERS substrates, including Klarite substrates [31], Q-SERS substrates ™ [36], graphene-gold film-gold nanorod [37], solid-phase extraction-SERS [20], gold nanoparticles functionalized glycidyl methacrylate-ethylene dimethacrylate [21] substrates. It is clearly observed that the SERS column we reported has a best position among the SERS substrates, and is as good as other techniques.…”
Section: Determination Of Phosmetmentioning
confidence: 99%